Exploring and exploiting the systemic effects of deregulated replication licensing - Petrakis, Theodoros G.; Komseli, Eirini Stavroula; Papaioannou, Marilena; Vougas, Kostas; Polyzos, Alexandros; Myrianthopoulos, Vassilios; Mikros, Emmanuel; Trougakos, Ioannis P.; Thanos, Dimitris; Branzei, Dana; Townsend, Paul; Gorgoulis, Vassilis G (Seminars in Cancer BiologySeminars in Cancer Biology, 2016)
Maintenance and accurate propagation of the genetic material are key features for physiological development and wellbeing. The replication licensing machinery is crucial for replication precision as it ensures that replication takes place once per cell cycle. Thus, the expression status of the components comprising the replication licensing apparatus is tightly regulated to avoid re-replication; a form of replication stress that leads to genomic instability, a hallmark of cancer. In the present review we discuss the mechanistic basis of replication licensing deregulation, which leads to systemic effects, exemplified by its role in carcinogenesis and a variety of genetic syndromes. In addition, new insights demonstrate that above a particular threshold, the replication licensing factor Cdc6 acts as global transcriptional regulator, outlining new lines of exploration. The role of the putative replication licensing factor ChlR1/DDX11, mutated in the Warsaw Breakage Syndrome, in cancer is also considered. Finally, future perspectives focused on the potential therapeutic advantage by targeting replication licensing factors, and particularly Cdc6, are discussed.
Keywords: Cancer; Cdc6; Cdt1; Replication licensing factors; Replication stress